Analisis Struktur Ekonomi Daerah dengan Pendekatan Location Quotient, Shift Share Klasik, Dynamic LQ dan Esteban-Marquillas Shift Share - Arjuniadi, Arjuniadi; Nur, Muhammad; Zukifli, Zukifli; Herizal, Herizal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study analyzes the economic structure of Pidie Regency from 2018 to 2022 using the Location Quotient (LQ), Shift-Share Analysis (SSA), Dynamic Location Quotient (DLQ), and Esteban-Marquillas Shift-Share Analysis (SS-EM) approaches. Identifying leading sectors is crucial for supporting regional development planning. The LQ results indicate that only two sectors qualify as leading sectors, namely Agriculture, Forestry, and Fisheries and Other Services, while other sectors are classified as non-basic with relatively lower contributions compared to Aceh Province as the reference region. The SSA analysis reveals that although Pidie Regency exhibits overall competitive economic growth, its structural growth rate is slower compared to the reference region. DLQ results indicate that while the Agriculture, Forestry, and Fisheries sector is a dominant sector, it is classified as non-prospective due to its slower growth compared to other sectors at the provincial level. In contrast, the Transportation and Warehousing sector emerges as the most prospective sector, demonstrating significantly stronger growth compared to others. Meanwhile, the SS-EM analysis highlights that the Construction sector possesses the highest competitiveness, whereas most other sectors experience negative competitiveness. Some sectors, such as Information and Communication, Education Services, and Real Estate, hold potential as primary drivers of future economic growth if supported by appropriate policies. This study concludes that policy innovations and targeted sectoral development strategies are essential to achieving sustainable economic growth in Pidie Regency.